Synthesis and Hydrogenation of Heavy Homologues of Rhodium Carbynes: [(Me3P)2(Ph3P)Rh≡E‐Ar*] (E=Sn, Pb). Issue 11 (1st February 2021) - Widemann, Max; Eichele, Klaus; Schubert, Hartmut; Sindlinger, Christian P.; Klenner, Steffen; Pöttgen, Rainer; Wesemann, Lars
Abstract: Tetrylidynes [(Me3 P)2 (Ph3 P)Rh≡SnAr*] (10 ) and [(Me3 P)2 (Ph3 P)Rh≡PbAr*] (11 ) are accessed for the first time via dehydrogenation of dihydrides [(Ph3 P)2 RhH2 SnAr*] (3 ) and [(Ph3 P)2 RhH2 PbAr*] (7 ) (Ar*=2, 6‐Trip2 C6 H3, Trip=2, 4, 6‐triisopropylphenyl), respectively. Tin dihydride 3 was either synthesized in reaction of the dihydridostannate [Ar*SnH2 ] − with [(Ph3 P)3 RhCl] or via reaction between hydrides [(Ph3 P)3 RhH] and 1 / 2  [(Ar*SnH)2 ]. Homologous lead hydride [(Ph3 P)2 RhH2 PbAr*] (7 ) was synthesized analogously from [(Ph3 P)3 RhH] and 1 / 2  [(Ar*PbH)2 ]. Abstraction of hydrogen from 3 and 7 supported by styrene and trimethylphosphine addition yields tetrylidynes 10 and 11 . Stannylidyne 10 was also characterized by 119 Sn Mössbauer spectroscopy. Hydrogenation of the triple bonds at room temperature with excess H2 gives the cis ‐dihydride [(Me3 P)2 (Ph3 P)RhH2 PbAr*] (12 ) and the tetrahydride [(Me3 P)2 (Ph3 P)RhH2 SnH2 Ar*] (14 ). Complex 14 eliminates spontaneously one equivalent of hydrogen at room temperature to give the dihydride [(Me3 P)2 (Ph3 P)RhH2 SnAr*] (13 ). Hydrogen addition and elimination at stannylene tin between complexes 13 and 14 is a reversible reaction at room temperature. Abstract : Heavy rhodium carbynes featuring a Rh≡Sn or Rh≡Pb triple bond were synthesized via dehydrogenation of the respective rhodium dihydride complexes [(Ph3 P)2 RhH2 SnAr*] and [(Ph3 P)2 RhH2 PbAr*]. The syntheses were accomplished by reacting the nucleophilic organodihydridostannate with [(Ph3 P)3 RhCl] or in a hydride transfer reaction between [(Ph3 P)3 RhH] and organoelement hydrides of tin or lead.